Financial integration of East Asian economies : evidence from real interest parity - Ahmad Zubaidi, Baharumshah; Chan, Tze Haw; A. Mansur, M. Masih; Evan, Lau (Universiti Malaysia Sarawak, (UNIMAS), 2011)
In this article, we investigate the financial linkages between the East Asian economies with Japan and the United States. We test for long-run Real Interest-rate Parity (RIP) using an array of panel-data techniques, including recent techniques developed by Breuer et al. (2002 Breuer, JB, McNown, R and Wallace, MS. 2002. Series-specific unit root tests with panel data. Oxford Bulletin of Economics and Statistics, 64: 527–46. [CrossRef], [Web of Science ®]) and Carrion-i-Silvestre et al. (2005 Carrion-i-Silvestre, JL, Del Barrio-Castro, T and López-Bazo, E(CDL). 2005. Breaking the panels: an application to the GDP per capita. Econometrics Journal, 8: 159–75.[CrossRef], [Web of Science ®]). This study offers two important results: first, the failure to account for structural breaks in the industrialized countries and Asian emerging economies is likely to provide evidence of nonstationary series that are stationary. Second, we found strong evidence that the parity condition holds in all the Asian countries. The failure of earlier studies to confirm mean reversion of Real Interest-rate Differential (RID) may reflect the choice of estimation/testing procedure rather than any inherent deficiency in the RIP.